PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN TOTAL ASSETS TURNOVER TERHADAP PRICE BOOK VALUE (Studi Pada Sub Sektor Makanan dan Minuman yang Tercatat di Bursa Efek Indonesia Periode 2016-2020) - Rifqi Kurnia Nugraha; Iwan Firdaus (Universitas Mercu Buana, 2023)
This study aims to determine the effect of the current ratio, debt to equity ratio, return on equity, and total assets turnover on price book value. The pollution in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020 totaling 22 companies according to the characteristics determined by the researchers. Selection of the sample using purposive sampling method and obtained 22 companies. The data collection method uses data triangulation, using the company's annual financial report data obtained from the Indonesia Stock Exchange (IDX) website and each company's website. The research method is causality research using panel data regression. The research analysis used panel data regression with the selected model approach, namely the Fixed Effect Model. The results of the study show that the current ratio, total assets turnover has no effect on price book value. Meanwhile, for the variable debt to equity ratio, return on equity has a positive and significant effect on price book value.